Together at midnight - Castle, Jennifer (HarperTeen, an imprint of HarperCollins Publishers, 2018)
Teens Kendall and Max witness a tragic accident during the holidays and, racked with guilt, accept a dare to perform seven random acts of kindness to strangers by New Year's Eve.